MAJORANA Collaboration's Experience with Germanium Detectors. (April 2015) - Mertens, S; Abgrall, N; Avignone, F T; Barabash, A S; Bertrand, F E; Brudanin, V; Busch, M; Buuck, M; Byram, D; Caldwell, A S; Chan, Y-D; Christofferson, C D; et al.
Abstract: The goal of the Majorana Demonstrator project is to search for 0νββ decay in 76 Ge. Of all candidate isotopes for 0νββ, 76 Ge has some of the most favorable characteristics. Germanium detectors are a well established technology, and in searches for 0νββ, the high purity germanium crystal acts simultaneously as source and detector. Furthermore, p-type germanium detectors provide excellent energy resolution and a specially designed point contact geometry allows for sensitive pulse shape discrimination. This paper will summarize the experiences the MAJORANA collaboration made with enriched germanium detectors manufactured by ORTEC ®® . The process from production, to characterization and integration in MAJORANA mounting structure will be described. A summary of the performance of all enriched germanium detectors will be given.